Economic Policy from the Perspective of Siyasah Syar'iyyah: A Case Study of Islamic Banks - Tri Wahyudiono; Fathur Rochim; Juni Iswanto (Universitas Muhammadiyah Palu, 2022)
This study explores the implementation of economic policy from the perspective of Siyasah Syar'iyyah, focusing on Islamic banks as a case study. Siyasah Syar'iyyah, or Islamic governance, emphasizes the alignment of economic practices with Sharia law, aiming to promote public welfare (maslahah) and prevent harm (mafsadah). The research highlights how Islamic banks operate under unique principles that prohibit interest (riba) and advocate for profit-sharing arrangements, thereby fostering ethical financial practices. By analyzing various case studies, this paper examines the effectiveness of Islamic banking in contributing to economic development while adhering to Islamic principles. The findings indicate that Islamic banks play a crucial role in enhancing financial inclusion, supporting micro and small enterprises, and promoting social justice through their financial products. However, challenges such as regulatory constraints, political dynamics, and cultural resistance must be addressed to optimize the impact of these institutions. Ultimately, this research underscores the importance of integrating Siyasah Syar'iyyah into economic policymaking to achieve sustainable growth and equitable resource distribution.